Images processing: a mobile augmented reality prototype for vehicle parking / Abdulrauf Tosho ... [et al.] - Tosho, Abdulrauf; Sefinat, Muhammad-Thani; Oluseye, Akanni Abdulsabur; Omotayo, Adebayo Aminat (UiTM Cawangan Perlis, 2023)
The emergence of augmented reality has made unstructured data processing an interesting field of study. Augmented reality enhances the retrieval of vital information from text and images. This research is centered on the development of a prototype using augmented reality to reduce the problem of security issues inherent in the context that bothers cars parked. The prototype was based on an AR application that runs on a smartphone. It reads through the car plate number which immediately matches with the car information on the central database of the Federal Road Safety Corps. The AR-Information device displays the car owners' information on the reader's mobile screen. The prototype was implemented and the interview was carried out among 59 staff of Al-Hikmah University in Nigeria. The respondents were to evaluate the usability of the AR-Image Processing prototype. 97.72% of respondents agreed that the proposed AR-Information device has demonstrated high usability in reducing the problem in security that was inherited in the car park and found it interesting.